2012
DOI: 10.1002/ange.201202771
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Regioselective Carboacylation of Olefins: A CC Bond Activation Approach for Accessing Fused‐Ring Systems

Abstract: We thank UT Austin and CPRIT for a start-up fund. We also thank faculty members from the organic division at UT for their generous support. We acknowledge Dr. V. Lynch for X-ray crystallography. We thank A. Spangenberg and S. Sorey for their advice on NMR spectroscopy. We thank Johnson Matthew for a gift of rhodium salts. We thank Chiral Technologies for their generous donation of chiral HPLC columns. We appreciate the helpful discussions with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…(3)]. 6a We hypothesized that the use of monodentate π‐acidic ligands (inspired by a recent work of Tang9) would benefit the formation of the spirocycle in two different aspects: 1) the faster ligand exchange (compared to bidentate ligands) would facilitate the formation of open coordination sites on Rh, which in turn could favor both β‐H elimination and CO deinsertion; 2) the more electron‐deficient catalyst would coordinate more strongly with the trisubstituted olefins, thus enhancing subsequent migratory insertion 10 …”
Section: Methodsmentioning
confidence: 99%
“…(3)]. 6a We hypothesized that the use of monodentate π‐acidic ligands (inspired by a recent work of Tang9) would benefit the formation of the spirocycle in two different aspects: 1) the faster ligand exchange (compared to bidentate ligands) would facilitate the formation of open coordination sites on Rh, which in turn could favor both β‐H elimination and CO deinsertion; 2) the more electron‐deficient catalyst would coordinate more strongly with the trisubstituted olefins, thus enhancing subsequent migratory insertion 10 …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, under the optimized reaction conditions, low conversions were observed for these substrates. However, we recently discovered that using a Lewis acid as a cocatalyst can dramatically enhance the reaction rate of olefin carboacylation, likely because of its coordination with the carbonyl group promoting both oxidative addition and reductive elimination 4a. 18…”
Section: Methodsmentioning
confidence: 99%
“…As an important subset of various dicarbofunctionalization reactions, olefin aryl-acylation or aryl-carbamoylation allows for the synthesis of structurally complex carbonyl compounds directly starting from alkenes, and considerable progress has been accomplished in this domain. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, enantioselective variants of these reactions are still rare. [31][32][33][34] In 2012, Dong et al reported a one-component asymmetric version of aryl-acylation of alkenes employing strained benzocyclobutanones with a pendant olefinic unit as the precursors, which was efficiently catalyzed by a chiral rhodium complex (Figure A-1).…”
Section: Introductionmentioning
confidence: 99%